PELANGGARAN HAK KONSTITUSIONAL MENGENAI MULTITAFSIR PASAL 164 AYAT (3) UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Irma Dewi Anggraini (Lex Renaissance, 2021)
This study raises issues of first, regarding the violation of constitutional rights that occurred in Article 164 paragraph (3) of Law Number 13 of 2003 on Manpower. Second, as a result of the multiple interpretations that occurred in Article 164 paragraph (3) of Law Number 13 of 2003 on Manpower. The research method used in this research is normative juridical. The approach used in this research is a statutory approach. The results of the research are first, there are multiple interpretations in Article 164 paragraph (3) of Law Number 13 of 2003 on Manpower, so that the rights of workers are violated by employers. Second, due to multiple interpretations of Article 164 paragraph (3) of Law Number 13 of 2003 on Manpower (i) employers can misuse it to give layoffs to workers/laborers; (ii) employers in terms of doing layoffs must be interpreted as a last resort; (iii) a review is submitted; (iv) employers should be held accountable for the loss of livelihoods for workers. Key Words: Constitutional rights; multiple interpretationsAbstrakPenelitian ini mengangkat permasalahan, pertama, mengenai pelanggaran hak konstitusional yang terjadi dalam Pasal 164 ayat (3) Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan. Kedua, akibat dari multitafsir yang terjadi pada Pasal 164 ayat (3) Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan. Metode penelitian yang digunakan dalam penelitian ini adalah yuridis normatif. Pendekatan yang dipergunakan dalam penelitian adalah pendekatan perundang-undangan (statue approach). Hasil penelitian bahwa, pertama, terdapat multitafsir dalam Pasal 164 ayat (3) Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan, sehingga  hak-hak pekerja dilanggar oleh pengusaha. Kedua, akibat adanya multitafsir terhadap  Pasal 164 ayat (3) Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan (i) dapat disalahgunakan oleh pengusaha untuk memberikan PHK kepada pekerja/buruh; (ii) pengusaha dalam hal melakukan PHK harus dimaknai sebagai upaya terakhir; (iii) diajukan Peninjauan Kembali; (iv) pengusaha harus bertanggungjawab atas hilangnya mata pencaharian para pekerja.Kata Kunci: Hak konstitusional; multitafsir